The role of psychological security climate, leadership, and self-efficacy on teachers capability through knowledge management - Edy Siswanto; Samsudi Samsudi; Eko Supraptono; Yeri Sutopo (Institute of Advanced Engineering and Science, 2024)
The study analyzed the relationship of leadership to knowledge management, leadership to innovation capability, psychological security climate to knowledge management, psychological security climate to innovation capability, self-efficacy to knowledge management, self-efficacy to innovation capability, knowledge management to innovation capability. The unit of analysis was vocational teachers and principals of vocational schools. The number of teachers from the respondents education unit is 3,056 teachers. By using the Slovin formula, the minimum number of sample sizes is 354 people and the sampling technique used was simple random sampling. The data analysis technique in this study uses partial least square (PLS). The results of data processing show that leadership has a significant effect on knowledge management, leadership has a significant effect on innovation capability, psychological security climate has a significant effect on knowledge management, psychological security climate has a significant effect on innovation capability, self-efficacy has a significant effect on knowledge management, self-efficacy has a significant effect on innovation capability, knowledge management has a significant effect on innovation capability. This research contributes to improving the quality of curriculum, teachers, and graduates of vocational schools/polytechnics in the 21st century.